Sensitization to house dust mites in Reykjavik, Iceland, in the absence of domestic exposure to mites - Hallas, T E; Gislason, D; Bjornsdottir, U S; Jorundsdottir, K B; Janson, C; Luczynska, C M; Gislason, T (Allergy, 2004)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field BACKGROUND: House dust mites are common sources of indoor allergens. In Reykjavik, Iceland, 9% of the young adult population had serum-specific IgE to Dermatophagoides pteronyssinus. Sensitization to mites is usually assumed to be due to exposure to house dust mites in the indoor environment. This investigation was carried out to measure the concentrations of house dust mite allergens and to investigate which species of mites were present in beds in Iceland. METHODS: A total of 197 randomly selected adults were visited at home using the European Community Respiratory Health Survey (ECRHS) II Indoor protocol. Dust samples were collected from mattresses for measurement of house dust mite allergen concentrations and to estimate the number and type of house dust mites. Additional samples from mattresses and floors were collected from the homes of 10 patients with positive skin prick tests (SPT) to D. pteronyssinus. House dust mite allergen concentrations were measured using ELISA and examination of mite species was carried out using microscopy. Climatic parameters were assessed using psychrometer readings in the bedrooms and outdoors. RESULTS: We found two single mite specimens, both D. pteronyssinus, in two dust samples. Mite allergen analyses indicated that two other dust samples had Der f 1 results close to the cut-off of 0.1 microg/g of dust. No samples were positive for Der p 1. In an additional collection of dust from the homes of 10 SPT-positive patients no Dermatophagoides spp. were found. CONCLUSIONS: Reykjavik citizens are exposed to extremely low amounts of house dust mite allergens in their homes. Possible alternative sources for sensitization are discussed, such as bird nests, exposure from travelling abroad, or other mites or invertebrates that cross-react with house dust mite allergens. Our findings suggest that exposures other than to house dust mites indoors are possible sources of mite ...